PENGARUH PENGAWASAN KERJA, DISIPLIN KERJA, DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN GIANYAR - Ni Komang Novi Sugiantari; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (VALUES, 2023)
This study aims to determine the effect of work supervision, work discipline, and work stress on employee performance at the Office of the Regional Financial and Asset Management Agency (BPKAD) Gianyar Regency. This research was conducted at the Office of the Gianyar Regency Regional Financial and Asset Management Agency which is located at JL. Ciung Wanara No. 16, Gianyar. The population in this study were all employees at the Office of the Regional Financial and Asset Management Agency, Gianyar Regency. Sampling in this study using the saturated sample method, obtained 98 respondents. The analytical method used is multiple linear regression analysis. The results showed that work supervision had a positive and significant effect on employee performance, work discipline had a positive and significant effect on employee performance, and work stress had no positive and significant effect on employee performance. The work discipline variable is the most dominant variable influencing employee performance.